(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Zheng C, Zhu J, Yang X, Fu B. 2022. Short Communication: Genetic diversity of walnut blight-associated bacteria from China using rep-PCR. Biodiversitas 23: 5681-5686. Walnut blight is caused by the bacterium Xanthomonas arboricola pv. juglandis (Xaj), is one of the most serious diseases in walnut production around the world. Understanding the genetic diversity of walnut blight pathogen is of great significance to developing a scientific and reasonable prevention and control strategy. The rep-PCR (Repetitive Sequence Polymerase Chain Reaction) technique is a powerful tool for analyzing plant pathogens. In this paper, using three pairs of rep-PCR universal primers (ERIC, BOX, and REP), a genetic diversity analysis was carried out on walnut blight-associated bacteria mainly isolated from different counties of Hubei Province, China. A study of 60 walnut blight-associated bacteria isolated in 2016 found that they had a high genetic similarity among them. There is no clear correlation between the genetic diversity of these isolates and their geographical or tissue origins. Interestingly, these clusters can also distinguish copper-resistant isolates from sensitive ones. Therefore, rep-PCR is a powerful tool to study the population of walnut pathogenic bacteria.